Maternal high fat diet-induced obesity affects trophoblast differentiation and placental function in mice. Issue 6 (11th September 2020) - Kretschmer, Tobias; Turnwald, Eva-Maria; Janoschek, Ruth; Zentis, Peter; Bae-Gartz, Inga; Beers, Tim; Handwerk, Marion; Wohlfarth, Maria; Ghilav, Mojgan; Bloch, Wilhelm; Hucklenbruch-Rother, Eva; Dötsch, Jörg; et al.
Abstract: Evidence suggests that maternal obesity (MO) can aggravate placental function causing severe pathologies during the perinatal window. However, molecular changes and mechanisms of placental dysfunction remain largely unknown. This work aimed to decipher structural and molecular alterations of the placental transfer zone associated with MO. To this end, mice were fed a high fat diet (HFD) to induce obesity before mating, and pregnant dams were sacrificed at E15.5 to receive placentas for molecular, histological, and ultrastructural analysis and to assess unidirectional materno-fetal transfer capacity. Laser-capture microdissection was used to collect specifically placental cells of the labyrinth zone for proteomics profiling. Using BeWo cells, fatty acid-mediated mechanisms of adherens junction stability, cell layer permeability, and lipid accumulation were deciphered. Proteomics profiling revealed downregulation of cell adhesion markers in the labyrinth zone of obese dams, and disturbed syncytial fusion and detachment of the basement membrane (BM) within this zone was observed, next to an increase in materno-fetal transfer in vivo across the placenta. We found that fetuses of obese dams develop a growth restriction and in those placentas, labyrinth zone volume-fraction was significantly reduced. Linoleic acid was shown to mediate beta-catenin level and increase cell layer permeability in vitro. Thus, MO causes fetal growth restriction, molecular and structural changes in the transfer zone leading to impaired trophoblast differentiation, BM disruption, and placental dysfunction despite increased materno-fetal transfer capacity. These adverse effects are probably mediated by fatty acids found in HFD demonstrating the need for obesity treatment to mitigate placental dysfunction and prevent offspring pathologies. Abstract : High fat diet-induced, murine maternal obesity is associated with fetal growth restriction, an impaired trophoblast differentiation and basement membrane disruption in the placental labyrinth zone which could cause an increased materno-fetal transfer.